2009
DOI: 10.1007/s12253-009-9191-8
|View full text |Cite
|
Sign up to set email alerts
|

Decreased p21 Expression in HPV-18 Positive Cervical Carcinomas

Abstract: The aim of this study was to investigate the relationship between different human papillomavirus (HPV) genotypes and the expression of p53, p21 and p27 in cervical carcinomas. A total of 103 cases of cervical carcinomas were assayed for expression of p53, p21 and p27 by immunohistochemistry. HPV typing was carried out by two polymerase chain reaction-based methods. Overall, HPV prevalence was 97.1% among the cervical carcinomas in this study. HPV-16 was detected in 66% of the tumors, HPV-18 in 7.8%, HPV-16/18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…These findings demonstrate that cells expressing HPV18E6 efficiently degraded p53, leading to the inactivation of the p21and the inability to protect against cellular transformation ( 46 ). This finding is consistent with other studies that have shown that p21 gene transcription is inhibited by HPVE6-mediated p53 degradation and that its reduced expression is also observed in invasive squamous cell carcinomas ( 18 , 47 , 48 ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings demonstrate that cells expressing HPV18E6 efficiently degraded p53, leading to the inactivation of the p21and the inability to protect against cellular transformation ( 46 ). This finding is consistent with other studies that have shown that p21 gene transcription is inhibited by HPVE6-mediated p53 degradation and that its reduced expression is also observed in invasive squamous cell carcinomas ( 18 , 47 , 48 ).…”
Section: Discussionsupporting
confidence: 93%
“…As a sexually transmitted agent, HPV are involved in transformation and maintaining of transformed status ( 47 ). Many studies have reported that HPV can also alter the expression of p21 ( 48 50 ). Thus, we searched the GEO dataset to seek for information about the relationship between MNX1 and HPV viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, p27 was reported to decrease from normal cases to carcinoma (Cheung et al, 2001). On the other hand, Huang et al (2010) reported that p21 expression decreased in HPV 18 positive carcinomas. The fact that aberrant expression of p27, cyclin E and p16 are early events in carcinogenesis (while p21 occur late in cervical carcinogenesis) might be of interest for early diagnostic and for monitoring patients with cervical dysplasia (Bahnassy et al, 2007).…”
Section: Cell Cycle Regulation Markersmentioning
confidence: 99%